Hitler's courts : betrayal of the rule of law in Nazi Germany - Greene, Joshua, 1950-; Kumar, Shiva, 1960-; Stories To Remember (Firm); Jacob D. Fuchsberg Law Center; Soundview Media Partners ([Old Westbury, N.Y.] : Stories to Remember, 2006)
When those charged with defending the rule of law betray that trust, the victory of tyrants is assured. Hitler's Courts features archival footage from the Nazi era, rarely seen photographs, and interviews with leading voices in international law. Experts examine the perversion of the courts under Nazi rule and discuss how distinguished lawmakers were capable of complicity in the largest mass murder of men, women and children in history.
Originally released as a motion picture in 2005.
Narrated by Joshua M. Greene.
Cinematographer and editor, Shiva Kumar ; music, Steve Gorn.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 12, 2020)
Keywords: Holocaust, Jewish (1939-1945); National socialism and justice; Criminal justice, Administration of -- History; Lawyers -- Germany -- History; Germany -- Politics and government; War crime trials -- Germany -- Nuremberg -- History; Documentary films; Historical films; Nonfiction films; Internet videos; Streaming video